The Increasing of Preschool Multiple Intelligences by Educative Playing Instrument Stimulation - Yuni Sufyanti Arief; Ilya Krisnana; Heny Ferdiana; Praba Diyan Rachmawati (Jurnal Ners, 2012)
Introduction: Multiple Intelligences can be incresed by playing stimulation with educative playing instrument. Educative playing is the activity that uses educate ways and instrument. Educative playing very important to increase speech development, cognitive, socialisation with the environment and also increse the streght and skill of child’s body.Methods: Design used in this study was quasy experiment design. The population was preschool children 4–5 years old in working area of Mojo Public Health Centre of Surabaya. The sample was preschool children 4–5 years old that spesiﬁc in inclution criteria of this study. Data were analyzed by wilcoxon signed rank test to compare the ordinal data pre and post intervention and mann withney u-test that compare between intervention group and control group with level of signiﬁ cance of α ≤ 0.05.Results: The result of speech development that analyzed by Wilcoxon signed rank test showed that controlled group had p = 0.157 and intervention group had p = 0.005 and the result of mann whitney test was p = 0.03. The result of kinesthetic development by wilcoxon signed rank test showed that controlled group has p = 0.317 and intervention group has p = 0.005, and analyzed by mann whitney test in kinesthetic development showed the result of p = 0.02.Conclusion: Educative playing instrument (picture cards, play dough, origami and meronce) increased speech and ﬁne motoric development of preschool children 4–5 years old in Mojo Indah Kindergarten of Surabaya. Educative playing instrument is the activity that makes the playing function optimally in child development and this activity can increase the child development such as physical, speech, cognitive and social adaptation.